APPLICATION OF INNOVATIVE EDUCATIONAL METHODS IN TEACHING MEDICAL AND PHARMACEUTICAL DISCIPLINES - Новикова Лариса Георгіївна; Марченко-Толста Катерина Сергіївна; Білан Ольга Анатоліївна (International Journal of Innovative Technologies in Social Science, 2023)
The article examines the peculiarities of the generation of modern students and teachers involved in the educational process from the point of view of generational theory and modern ideas about general and professional competencies in medical/pharmaceutical higher education. Innovative approaches and methods, and modern educational technologies used in teaching medical and pharmaceutical disciplines are summarised, and the prospects for transition to a new design of the educational space are analyzed.